Efficacy of COVID-19 vaccines among healthcare workers in the Kingdom of Saudi Arabia - Zainah M. Al Shahrani; Yahya I. Alnshbah; Safaa A. Fallatah; Tabish Humayun; Ghazail M. Albeshi; Nawal M. Alanazi; Fayze Z. Aldalbehi; Eman A. Barnawi; Nawaf M. Almatrafi; Dalal H. Almutairi; Alhanouf A. Aldarami; Rayed A. Alasiri; et al. (Journal of Clinical Virology Plus, 2025)
Background: Although COVID-19 vaccinations prevent infection, certain cases have been documented even after vaccination. This has raised questions regarding their safety and effectiveness. Aim: Evaluating the efficacy of COVID-19 vaccines among healthcare workers in Saudi Arabia and assessing the severity of post-vaccination infection. Subject and Methods: A cross-sectional design enrolling 124,742 healthcare workers (HCWs) with PCR-confirmed COVID-19 infection from March 2020 to March 2022. They were divided into two groups based on their vaccination status: a pre-vaccination group and a post-vaccination group. The data collected were obtained from the following hospitals (MOH, governmental non-MOH, and Private hospitals). Statistical analyses were performed using SPSS version 25. Results: The overall mean COVID-19 positivity rates among the HCWs were higher following vaccination and were found to be 52.88 % (n = 65,968) compared to 47.12 % (n = 58,774) in the pre-vaccination group. The mortality and ICU admission rates significantly decreased in the post-vaccination group (36.5 % and 40.9 %) than pre-vaccination (63.5 % and 59.1 %). The cure rate increased significantly from 47.0 % in pre-vaccination to 53.0 % in the post-vaccination group. Gender, nationality, job title, hospital category, and vaccine type were all associated with a significantly higher risk of infection following vaccination (p > 0.05). Conclusion: Vaccinated healthcare personnel remain susceptible to infection and should be instructed to take all necessary infection control precautions to avoid future COVID-19 pandemics. Rigorous oversight of the private sector is essential for conducting focused audits and evaluations of infection control policies in private healthcare environments.